Kekerasan Dalam Rumah Tangga Pada Film Bolehkah Sekali Saja Kumenangis 2024: Analisis Wacana Kritis Model Van Dijk - Annisa Zahrani Fahira Naafita Sari; Syafrida Nurrachmi Febriyanti (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET), 2026)
The issue of domestic violence in Indonesia has a high number of cases, so it is often raised in a film. This study analyzes the discourse of domestic violence in the film